Pedagogical conditions for the formation of eco-values of future teachers of natural sciences: a methodological approach - Rogoza, Valentin (ScienceRise: Pedagogical Education, 2020)
The urgency of forming an eco-focused type of understanding nature among modern people has a philosophical and theoretical justification and practical confirmation, related to the sad experience of environmental problems. In turn, this actualizes the task of introducing into the educational process pedagogical conditions, which would stimulate the formation of environmental values of specialists in the specialty 014.15 General Education (Natural Sciences) of the first (bachelor’s) level of higher education. These specialists can be potential adherents of the eco-focused type of understanding nature. This task is even more relevant, considering the fact that the axiological component in modern educational programs of the relevant profile is not enough represented little, and the formation of environmental value competencies is not their goal. The purpose of this study is to clarify the content of the methodological approach regarding verifying the effectiveness of the implementation of certain pedagogical conditions in order to obtain the desired educational result – the formation of environmental values in future teachers of natural sciences. The research has generalized and systematized scientific methods, which allow determining the effectiveness of pedagogical conditions for the formation of environmental values through the implementation of the author’s course “Axiological Pedagogy” and training course “Ensuring the adoption and translation of professional values.” The paper presents for the first time a methodological research system that is justified for the analysis of the first systematized and substantiated environmental values as the desired results of the educational process. The article defines peculiarities of application of methods for diagnosing the formation of ecological values in future teachers of natural sciences. The pilot test of the described methodological research system has proved its validity in pedagogical practice, in particular, to assess the results of the implementation of pedagogical conditions for the formation of environmental values of specialists in specialty 014.15 Secondary education (Natural Sciences) of the first (bachelor’s) level of higher education